Pengaruh Standar Sarana dan Prasarana terhadap Motivasi Kerja Guru Daycare - Widyawati, Widyawati; Rizki Tiara, Dinda (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Trunojoyo Madura, 2024)
This study aims to determine the influence of facilities and infrastructure standards on the work motivation of daycare teachers. The research employs a quantitative approach, utilizing simple linear regression and correlation analysis. The study was conducted in Pamekasan Regency, encompassing all 30 daycare teachers through a saturated sampling technique. Data were collected via an online questionnaire using a Likert scale. Validity testing with 30 respondents revealed that the significance values for variables X and Y were 0.004 < 0.05, indicating the validity of all items for both variables. Reliability testing yielded a Cronbach's alpha coefficient of 0.931 for variable X and 0.852 for variable Y, both exceeding the 0.6 threshold, thus confirming the reliability of the items for both variables. Normality testing showed a significance value of 0.150 > 0.05, suggesting a normal distribution of residuals. Homogeneity testing resulted in a value of 0.601 > 0.05, indicating homogeneous data. The correlation test indicated a significance value of 0.004 < 0.05, demonstrating a correlation between the two variables. The simple linear regression analysis produced an F value of 9.608, which is greater than the F table value of 4.196, with a significance level of 0.004 < 0.05. This indicates that the standards of daycare facilities and infrastructure significantly influence the work motivation of daycare teachers. The correlation coefficient of 0.505 translates to 50.5%, suggesting that the facilities and infrastructure variable (X) accounts for 50.5% of the variance in the work motivation of daycare teachers (Y).